Ból brzucha jako częsta przyczyna interwencji medycznych lekarzy pierwszego kontaktu = Abdominal pain as a common cause of medical interventions by primary care physicians - Putowski, Maciej; Podgórniak, Marta; Piróg, Marta; Zawiślak, Jacek; Opielak, Grzegorz; Cyganok, Mikołaj; Smoleń, Agata Barbara (Journal of Education, Health and Sport, 2016)
Putowski Maciej, Podgórniak Marta, Piróg Marta, Zawiślak Jacek, Opielak Grzegorz, Cyganok Mikołaj, Smoleń Agata. Ból brzucha jako częsta przyczyna interwencji medycznych lekarzy pierwszego kontaktu = Abdominal pain as a common cause of medical interventions by primary care physicians. Journal of Education, Health and Sport. 2016;6(7):359-366. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57981 http://ojs.ukw.edu.pl/index.php/johs/article/view/3699 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 15.07.2016. Ból brzucha jako częsta przyczyna interwencji medycznych lekarzy pierwszego kontaktu Abdominal pain as a common cause of medical interventions by primary care physicians Maciej Putowski1, Marta Podgórniak1, Marta Piróg1, Jacek Zawiślak1, Grzegorz Opielak2, Mikołaj Cyganok3, Agata Smoleń4 1 Studenckie Koło Naukowe przy Katedrze i Zakładzie Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie 2 Katedra i Zakład Anatomii Prawidłowej, Uniwersytet Medyczny w Lublinie 3 Katedra i Zakład Medycyny Nuklearnej, Uniwersytet Medyczny w Lublinie 4 Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie Streszczenie Wstęp. Ból brzucha stanowi częstą przyczynę interwencji medycznych obserwowanych w jednostkach POZ, Nocnej i Świątecznej Opieki Zdrowotnej, na Izbie Przyjęć czy w Szpitalnych Oddziałach Ratunkowych. W związku z niespecyficznością tego objawu, wymaga on od lekarza wiedzy i zdolności do przeprowadzenia szybkiej i trafnej diagnostyki różnicowej, zwłaszcza u pacjentów z szybko pogarszającym się stanem ogólnym. W większości przypadków ból brzucha stanowi przejaw chorób narządów jamy brzusznej, w szczególności przewodu pokarmowego. Należy jednak pamiętać, iż może manifestować patologie zlokalizowane w innych okolicach ciała lub być wyrazem chorób ogólnoustrojowych: metabolicznych, neurogennych, naczyniopochodnych czy zatruć. Cel Pracy. Celem pracy była ocena częstości interwencji medycznych z powodu zgłaszanych przez pacjenta dolegliwości bólowych brzucha na przykładzie Szpitalnego Oddziału Ratunkowego w Janowie Lubelskim w latach 2004-2010. Materiał i Metody. Informacje zaczerpnięto z analizy książki przyjęć SOR w Janowie Lubelskim. Analizie poddane zostały wszystkie przypadki pacjentów z dolegliwościami bólowymi brzucha, którzy zgłosili się do SOR. Grupa pacjentów uwzględnionych w badaniu obejmowała osoby hospitalizowane na oddziale SOR, które w późniejszym czasie nie zostały skierowane na oddział specjalistyczny. Wyniki. Najczęstszą przyczyną bólu brzucha wśród zdiagnozowanych pacjentów było zapalenie błony śluzowej żołądka, które stanowiło 49,9% wszystkich przypadków. Częstymi przyczynami zgłoszenia do Szpitalnego Oddziału Ratunkowego były także: kolka nerkowa (23,0%) oraz kolka żółciowa (3,7%). Wnioski. Ból brzucha stanowi jeden z najczęstszych powodów zgłaszania się pacjentów do Szpitalnego Oddziału Ratunkowego. W większości przypadków objaw ten stanowi przejaw chorób przewodu pokarmowego, a jako najczęstszą z przyczyn wyróżnić należy zapalenie błony śluzowej żołądka. Słowa kluczowe: ból brzucha, szpitalny oddział ratunkowy, diagnostyka. Key words: abdominal pain, emergency room, diagnostics. Abstract Background. Abdominal pain is a common cause of medical interventions, both in Primary Care, Night and holiday Patient Care, Admissions and in the Hospital Emergency Department. As a result of low specificity of this symptom, it requires a doctor's knowledge and ability to perform quick and accurate differential diagnosis, especially in patients with rapidly deteriorating health. In most cases abdominal pain is a symptom of diseases of the abdominal organs, especially the digestive tract, but it should be marked that it may be a manifestation of pathology located in other areas of the body or it can be an expression of systemic diseases: metabolic, neurogenic, vascular or poisoning. Objectives. The aim of the study was to evaluate the percentage of medical interventions because of the patient’s reported pain in the abdomen on the example of Emergency Department in Janow Lubelski in 2004-2010. Material and Methods. The data were taken from analysis of the admission book from Emergency Departement in Janów Lubelski. Data analysis included patients that arrived at the Emergency Department with an abdominal pain. The group of examinated patients involved persons hospitalized on the Emergency Ward, without further referral to the departments. Results. The most common cause of abdominal pain in patients was gastritis, which accounted for 49.9% of all cases. Common causes of arriving at the Hospital Emergency Ward were also: renal colic (23.0%) and biliary colic (3.7%). Conclusions. Abdominal pain is one of the most common reasons for patients' arriving at the Hospital Emergency Ward. In most cases, this is a manifestation of diseases of the gastrointestinal tract, and the most common diagnose was gastritis.